Sustentabilidade Organizacional: A Proposição de uma Framework Representativa do Agir Competente para seu Acontecimento - Luciano Munck; Mariana Gomes Musetti Munck; Rafael Borim-de-Souza (Gerais, 2011)
The objective of this article is to propose a framework which shows the necessary processes for the occurrence ofthe corporate sustainability. The epistemological approach of this article is guided by the theory of organizationalaction, which observes the organization as a permanent process of actions and decisions which are disseminated inall managerial levels. Once that this logic has been chosen, another theory has been researched which couldcomplement the organizational acting with coherence in its actions and decisions. The competence theory has beenselected as a possible alternative. Through this interrelation between the organizational action, the corporatesustainability and the competence management, a framework has been structured showing the following mainpoints: a representative network of challenges necessary for the organization to reach its corporate sustainability; thegroup of competences needed to validate the reach of the corporate sustainability and the validation of theinterconnection of these two phenomena as a managerial precept able of inserting the sustainability principles in theorganizational actions and decisions.